2010
DOI: 10.5021/ad.2010.22.3.370
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Malignant Melanoma Associated with Papillary Thyroid Cancer

Abstract: As the survival from cutaneous malignant melanoma and its clinical concerns have been steadily increasing, the possibility has been raised of an increased risk of second primary cancers in the patients with malignant melanoma. Especially, recent studies have identified an association between cutaneous malignant melanoma and thyroid carcinoma. We here report on a case of cutaneous malignant melanoma that developed in a 61-year-old female patient who had hypothyroidism caused by papillary thyroid carcinoma. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…In our analysis of the literature, population-based studies that stratified SIR by time yielded mixed and inconclusive results, with some reports of increased risk in the first year and some reports of an increased risk up to ten years following the primary cancer diagnosis. In the six case reports of incidental TC diagnosed among CM patients that were excluded from our analysis, all cases of the subsequent cancer were detected during surveillance for the primary cancer: three cases were identified by FDG-PET for metastatic melanoma evaluation; one case was identified when routine pre-op laboratory exam for melanoma excision revealed abnormal thyroid levels; one case was diagnosed when routine dermatologic exam was significant for enlarged thyroid gland 8 months after excision of CM; and another case was diagnosed when radical neck dissection for CM metastasis to sentinel lymph node revealed metastasis of PTC in four out of thirty-eight lymph nodes [26][27][28][29][30]. Therefore, increased medical surveillance still could explain part of the association between TC and CM.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis of the literature, population-based studies that stratified SIR by time yielded mixed and inconclusive results, with some reports of increased risk in the first year and some reports of an increased risk up to ten years following the primary cancer diagnosis. In the six case reports of incidental TC diagnosed among CM patients that were excluded from our analysis, all cases of the subsequent cancer were detected during surveillance for the primary cancer: three cases were identified by FDG-PET for metastatic melanoma evaluation; one case was identified when routine pre-op laboratory exam for melanoma excision revealed abnormal thyroid levels; one case was diagnosed when routine dermatologic exam was significant for enlarged thyroid gland 8 months after excision of CM; and another case was diagnosed when radical neck dissection for CM metastasis to sentinel lymph node revealed metastasis of PTC in four out of thirty-eight lymph nodes [26][27][28][29][30]. Therefore, increased medical surveillance still could explain part of the association between TC and CM.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers have reported the association between malignant melanoma and TC . The mechanism for this is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The association of cutaneous melanoma (CM) and thyroid cancer (TC) has been rarely described in the last years . Risk factors that are known to be associated with CM, such as ultraviolet radiation, are not known to predispose individuals to TC .…”
mentioning
confidence: 99%
“…Some studies have demonstrated that dysplastic melanocytic cells, which form GCN, are positive for prepro‐TRH message and thyrotropin‐releasing hormone (TRH) protein expression in reverse‐polymerase chain reaction/Southern blotting and immunocytochemistry, 18 and also express high levels of TSH. It is probable that this is related to the thyroid disorder that leads to the development of hypothyroidism under the condition of low levels of circulating thyroid hormone and concomitantly elevated TSH 19 . High levels of TSH cause significant activity of thyroid cells, with increased production of thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that this is related to the thyroid disorder that leads to the development of hypothyroidism under the condition of low levels of circulating thyroid hormone and concomitantly elevated TSH. 19 High levels of TSH cause significant activity of thyroid cells, with increased production of thyroid hormones. Cells then deplete stocks of iodine, which lowers hormone production.…”
Section: Discussionmentioning
confidence: 99%